Are Smart Textiles the Future of Innovation in Technology and Design? - Muñoz González, Ana María
This article explores the transformative impact of smart textiles, innovative materials that blend technology and design to address global challenges. Classified as passive, active, and ultra-smart, these textiles offer capabilities ranging from environmental responsiveness to intelligent adaptability. Advances in nanomaterials, sensors, artificial intelligence, and energy harvesting drive their applications in healthcare, agriculture, architecture, and aerospace. Despite progress, challenges like scalability and sustainability persist. Highlighting innovations from leading companies, this work underscores the need for interdisciplinary collaboration to realize the potential of smart textiles in reshaping industries, enhancing user experiences, and promoting a sustainable future.